Legal large language models (LLMs): legal dynamos or “fancifully packaged ChatGPT”? - Fife Ogunde (Discover Artificial Intelligence)
Abstract This brief comment considers the impact of large language models (LLMs) specifically designed for legal tasks. In the author’s view, conversations regarding the use of such LLMs in the legal profession have been considered from various extremes depending on those leading the conversation. A proper contextualization of the role of legal LLMs should be the aim.